Effect of the application of vermicompost and millicompost humic acids about the soybean microbiome under water restriction conditions - da Silva, Maura Santos Reis de Andrade; de Carvalho, Lucas Amoroso Lopes; Braos, Lucas Boscov; de Sousa Antunes, Luiz Fernando; da Silva, Camilla Santos Reis de Andrade; da Silva, Cleudison Gabriel Nascimento; Pinheiro, Daniel Guariz; Correia, Maria Elizabeth Fernandes; Araújo, Ednaldo da Silva; Colnago, Luiz Alberto; Desoignies, Nicolas; Zonta, Everaldo; et al. (Frontiers in Microbiology, 2022)
Humic substances (HSs) are constituent fractions of organic matter and are highly complex and biologically active. These substances include humic acids (HA), fulvic acids (FA), and humin. HS are known to stimulate the root system and plant growth and to mitigate stress damage, including hydric stress. Humic acids have already been reported to increase microbial growth, affecting their beneficial effect on plants. However, there is scarce information on whether HA from vermicompost and millicompost, along with Bradyrhizobium, improves the tolerance of soybean to water restriction. This study aimed to evaluate the responses of soybean plants to the application of vermicompost HA (HA-V) and millicompost (HA-M) along with Bradyrhizobium sp. under water restriction. The experiment was carried out in a greenhouse, and the treatments received Bradyrhizobium sp. inoculation with or without the application of HA from vermicompost and millicompost with or without water restriction. The results showed that HA provided greater soybean growth and nodulation than the control. The application of HA-M stimulated an increase in the richness of bacterial species in roots compared to the other treatments. After the application of water stress, the difference between the treatments disappeared. Microbial taxa were differentially abundant in plants, with the fungal fraction most affected by HA application in stressed roots. HA-V appears to be more prominent in inducing taxa under stress conditions. Although the results showed slight differences between HA from vermicompost and millicompost regarding plant growth, both humic acids promoted an increase in plant development compared to the control.